Mary Had a Little Lamb - Hale, Sarah Josepha Buell 1788-1879.; Huliska-Beith, Laura 1964- (New York : Marshall Cavendish Children, 2011)
Presents the traditional nursery rhyme that tells the story of a schoolgirl and her faithful pet lamb.
Keywords: Lambs -- Juvenile poetry; Nursery rhymes, American; Children's poetry, American; Lambs -- Poetry; Nursery rhymes; American poetry